Positive death attitudes and psychological well-being: examining the influence of the four immeasurables - Glushich, Alla; Wongpakaran, Nahathai; Wongpakaran, Tinakon; DeMaranville, Justin; Wedding, Danny (Frontiers in Public Health, 2025)
BackgroundThe global ageing population trend has heightened the need to understand various factors affecting geriatric well-being, including beliefs and attitudes about death. Positive perspectives about death, such as those gained from practicing maranasati (death contemplation in Buddhism), may enhance psychological resilience and prosocial behavior, key factors promoted in public mental health. Death reflection can encourage the development of the Four Immeasurable Minds (equanimity, loving-kindness, compassion, and sympathetic joy), Buddhist virtues that promote public harmony and enhance well-being.ObjectiveThe current study investigated whether positive beliefs and attitudes about death influenced well-being directly or indirectly through the Four Immeasurable Minds among older Thai Buddhists, contributing to culturally informed mental health strategies.Materials and methodsData were collected from 332 older adults in Northern Thailand. The study collected information on positive beliefs and attitudes about death using the Morana Questionnaire, well-being using the WHO-5 index (Thai), and Four Immeasurable Minds using the Four Immeasurable Inventory. The data were analyzed using mediation analysis, accounting for potential confounding variables.ResultsPositive beliefs about death had a significant and positive effect on well-being, and prosocial values mediated this relationship.ConclusionThe findings suggest that positive beliefs about death can promote prosocial values and contribute to a healthy sense of well-being among Buddhist Thai older adult. Integrating culturally adapted, mindfulness-based approaches into public mental health initiatives could support healthy aging, particularly in Buddhist communities. Further research should explore scalable interventions to promote psychological resilience in diverse older populations.